Reproductive Biology of Nile Tilapia (Oreochromis niloticus) in Lake Chamo, Ethiopia - Shishitu, Buchale; Tesfaye, Gashaw; W/yohans, Atnafu (Journal of Agriculture and Environmental Sciences, 2021)
The objectives of the study were to determine the breeding season, fecundity rate, size at first maturity and sex ratio of O. niloticus in Lake Chamo. Data (total length (TL), total weight (TW), sex, maturity stages and number of eggs) were collected. A total of 1,245 samples (968 females and 277 males) were collected during the sampling period (December 2019 to November 2020). The collected data were summarized using descriptive statistics (percentage, graphs, tables) and analyzed with the application of Microsoft Excel 2010 and Sigma plot 13.0 Software. There was significant deviation in sex ratio (Females: Males) from hypothetical 1:1 ratio (Ï‡2 = 393.0; p<0.05). The mean fecundity was 1,138 eggs/ fish and it was positively correlated with TL and TW. The size at first sexual maturity (TL50) was 23.4 and 22.0 cm for females and males respectively. The O. niloticus in Lake Chamo breeds throughout the year. The peak breeding season was observed from March to May and August to November. It is recommendable to reduce commercial fishing of O. niloticus during the peak breeding seasons in order to minimize the capture of breeding fish. The size at first maturity in the present study for both sexes was 23.6 cm which is too smaller than the earlier study (39.6 cm). This might be due to heavy fishing together with illegal fishing activities, fishing during the breeding season, breeding ground destruction by buffer zone agricultural practices around the lake. Therefore, appropriate fishery management tools such as closing season during peak breeding, buffer zone conservation and mesh size regulation should be implemented for sustainable fishery utilization in Lake Chamo.